Analysis of Antigens of Mycobacterium leprae by Interaction to Sera IgG, IgM, and IgA Response to Improve Diagnosis of Leprosy. (29th June 2014) - Kumar, Avnish; Parkash, Om; Girdhar, Bhawneshwar K.
Abstract : Till 2010, several countries have declared less than one leprosy patient among population of 10, 000 and themselves feeling as eliminated from leprosy cases. However, new leprosy cases are still appearing from all these countries. In this situation one has to be confident to diagnose leprosy. This review paper highlighted already explored antigens for diagnosis purposes and finally suggested better combinations of protein antigens of M. leprae versus immunoglobulin as detector antibody to be useful for leprosy diagnosis.